Rimpu: An Overview of Symbolic Meaning - Suryani Octavianingsih (IJECA (International Journal of Education and Curriculum Application), 2018)
This paper aims to describe the symbolic meaning of rimpu as a cultural identity of female in Bima community. There are some meanings behind the different ways of wearing rimpu between married and unmarried women. Rimpu colo is worn by married women while rimpu mpida and rimpu cili are worn by unmarried women. Data for this research were collected using interview with Bimanese natives and library research to find the symbols of the way of the rimpu is worn. The study found that there are special symbols of rimpu for married and married women, including religious and cultural symbols. Rimpu also indicates the woman’s status in the society.